2017
DOI: 10.1093/alcalc/agx082
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is Related to Personality Differences in Reward Sensitivity and Impulsivity

Abstract: Individuals with higher levels of fasting ghrelin are more sensitive to reward, but less sensitive to punishment. Higher ghrelin levels are also related to some aspects of impulsivity such as decreased self-control and increased likelihood of acting without thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…They also found that higher ghrelin levels were furthermore related to certain aspects of impulsivity such as decreased self‐control and increased likelihood of acting without thinking (Ralevski et al . ). In demonstrating that the association between ghrelin plasma concentrations and alcohol craving is mediated by mesolimbic cue reactivity, our results suggest that endogenous ghrelin influences craving via changes in mesolimbic brain activation.…”
Section: Discussionmentioning
confidence: 97%
“…They also found that higher ghrelin levels were furthermore related to certain aspects of impulsivity such as decreased self‐control and increased likelihood of acting without thinking (Ralevski et al . ). In demonstrating that the association between ghrelin plasma concentrations and alcohol craving is mediated by mesolimbic cue reactivity, our results suggest that endogenous ghrelin influences craving via changes in mesolimbic brain activation.…”
Section: Discussionmentioning
confidence: 97%
“…The authors demonstrated that ghrelin may augment hedonic and incentive responses to influence food intake. Individuals with higher ghrelin levels are more sensitive to reward and impulsive behavior [ 84 ]. However, chronic high-intensity intermittent training has no significant effect on appetite or food reward and plasma AG concentrations in obese individuals [ 85 ].…”
Section: Ghrelin Influences the Hedonic And Incentive Responses To Comentioning
confidence: 99%
“…Ghrelin concentrations correlate positively with alcohol craving (Addolorato et al, 2006, Koopmann et al, 2012, Leggio et al, 2012); baseline ghrelin levels are higher in AUD individuals who subsequently relapse, but lower in those able to maintain abstinence (Leggio et al, 2012). Furthermore, higher baseline fasting levels of ghrelin predict more reward sensitivity and impulsivity (Ralevski et al, 2018), traits associated with compulsive alcohol use (Belin et al, 2008, Everitt and Robbins, 2005). As mentioned, higher baseline ghrelin is also associated with more subjective rewarding effects of alcohol in healthy social drinkers (Ralevski et al, 2017).…”
Section: Ghrelin Alcohol and Substance Usementioning
confidence: 99%